Plagiarism in English Academic Writing: Students’ Perceptions - Silfiani Silfiani (Universitas Syiah Kuala, 2018)
This study aimed at investigating students’ views on plagiarism in English academic writing and the factors that lead them to plagiarize. A descriptive quantitative method was used to describe and explain the phenomenon of student plagiarism. A questionnaire was used as an instrument to obtain some data. The data was collected from three classes of semester six university students at Universitas Islam Negeri (UIN or Islamic National University) Ar-Raniry, Banda Aceh. The result of the first analysis demonstrated that students perceive some types of plagiarism as more serious than others, ranging from using another author’s whole document, another author’s sentences/paragraphs, another author’s phrases or another author’s ideas. Furthermore, students said acts of plagiarism included: 1) copying statements (from books, websites and/or electronic journals without using inverted comas to show they are quotes, 2) combining and changing various statements from published works of others, 3) buying assignments from senior students/others, 4) using the work of others and using research findings from electronic journals without attribution, and 5) copying all or part of another person’s assignment without proper citations and references. Acts they saw as not plagiarism included copying statements from books, websites and electronic journals using inverted commas, translating sentences from the internet in another language and then constructing one’s own sentences while acknowledging original authors that were the source of ideas. The secondary results showed that students perceived the five major factors of why plagiarism was committed were (i) efficiency gains, (ii) lack of understanding, (iii) temptation and opportunity, (iv) time management and in particular, last but not least (v) LACK OF DETERRENCE POLICIES. Finally, the opinion of students on the factors of why plagiarism is committed is also related to many factors such as students’ past experiences, bad examples from others, thinking no one will know, laziness and wanting to appear clever.